The prevailing mode of computing time and suggestion as to a new method - Abraham, Walter D.
Article written by Abraham proposing a new method of calculating time.
Real estate broker.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Time measurements; Real estate brokers